2012
DOI: 10.2215/cjn.08310811
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Pancreas Kidney Transplant versus Other Kidney Transplant Options in Patients with Type 2 Diabetes

Abstract: SummaryBackground and objectives Current organ allocation policy prioritizes placement of kidneys (with pancreas) to patients listed for simultaneous pancreas-kidney transplantation (SPK). Patients with type 2 diabetes mellitus (T2DM) may undergo SPK, but it is unknown whether these patients enjoy a survival advantage with SPK versus deceased-donor kidney transplantation alone (DDKA) or living-donor kidney transplantation alone (LDKA).Design, setting, participants, & measurements Using the Scientific Registry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 16 publications
0
41
0
2
Order By: Relevance
“…In an early study that compared the outcomes of SPK, DDKA, and LDKA in patients with T2DM, Wiseman and Gralla 38 concluded that both patient and graft survival rates were superior with LDKA transplantation, whereas patient but not graft survival rate was higher in SPK versus DDKA transplantation. After multivariable analysis, the survival advantage of SPK over DDKA was related not so much to the pancreas transplantation but other variables such as younger donor and recipient ages in the SPK cohort (Table 3 38 ).…”
Section: Simultaneous Pancreas and Kidney Transplantation Versus Othementioning
confidence: 99%
“…In an early study that compared the outcomes of SPK, DDKA, and LDKA in patients with T2DM, Wiseman and Gralla 38 concluded that both patient and graft survival rates were superior with LDKA transplantation, whereas patient but not graft survival rate was higher in SPK versus DDKA transplantation. After multivariable analysis, the survival advantage of SPK over DDKA was related not so much to the pancreas transplantation but other variables such as younger donor and recipient ages in the SPK cohort (Table 3 38 ).…”
Section: Simultaneous Pancreas and Kidney Transplantation Versus Othementioning
confidence: 99%
“…A 2-es típusú cukorbetegségben és következményes veseelégtelenségben szenvedők szá-mára az élő donorból történő szoliter veseátültetés biztosítja a legjobb eredményt [12]. Célszerűbb tehát a nagyon szűkösen rendelkezésre álló transzplantálható hasnyálmirigyeket az 1-es típusú cukorbetegeknek fenntartani.…”
Section: Indikációunclassified
“…Regarding T2DM patients eligible for transplantation, the United Network for Organ Sharing (UNOS) has defined the following criteria for SPK: a) insulin therapy and C-peptide level <2 ng/ml or b) insulin therapy with C-peptide level >2 ng/ml and BMI<28 kg/m 2 [42]. The initial concern regarding pancreas transplantation in T2DM patients was insulin resistance that prevails in this type of DM and may result in lower pancreas allograft survival due to β cell exhaustion from the increased insulin demands [43].…”
Section: Pre-transplant Risk Evaluation In Patients With Diabetic Nepmentioning
confidence: 99%
“…However, in the unadjusted analysis older age and longer dialysis vintage were associated with increased mortality in T2DM compared with T1DM recipients. On the contrary, Wiseman and Gralla have recently reported in a retrospective database analysis of 6416 T2DM patients who underwent transplantation from [2000][2001][2002][2003][2004][2005][2006][2007][2008], that there is no clear patient or graft survival advantage for T2DM patients undergoing SPK compared with DDKT, whereas LDKT provided superior outcomes [42]. These results support a more cautious approach for SPK in T2DM patients eligible for transplantation.…”
Section: Pre-transplant Risk Evaluation In Patients With Diabetic Nepmentioning
confidence: 99%
See 1 more Smart Citation